Answer:
-7/2 ±1/2sqrt(13) = x
Explanation:
f(x) =x^2 + 7x + 9
To find the zeros, set this equal to zero
0 = x^2 + 7x + 9
I will complete the square
Subtract 9 from each side
0-9 = x^2 + 7x + 9-9
-9 =x^2 + 7x
Take the coefficient of the x term, 7
divide by 2, 7/2
Then square it, (7/2)^2 = 49/4
Add this to both sides
-9 +49/4=x^2 + 7x + 49/4
-36/4 +49/4 = (x+7/2)^2
13/4 = (x+7/2)^2
Take the square root of each side
±sqrt(13/4) = sqrt( (x+7/2)^2)
± sqrt(13) /sqrt(4)= (x+7/2)
± 1/2 sqrt(13) = (x+7/2)
Subtract 7/2 from each side
-7/2 ±1/2sqrt(13) = x+7/2-7/2
-7/2 ±1/2sqrt(13) = x